Community-Based Learning Innovation and Student Motivation: An Evaluation of the Sinau Bareng Program in Surabaya, Indonesia - Mardiana, Dina; Pramono, Sapto; Widyawati, Widyawati; Mustofa, Amirul (Socious Journal, 2025)
This study aims to evaluate the implementation of social justice values in the context of social stratification in Indonesian society using a qualitative approach through literature review. This study begins with the phenomenon of increasing social, economic, and educational inequality, which indicates a gap between the ideal values of Pancasila and the social realities faced by society. Through an analysis of various scientific sources, this study identifies that the stratification structure formed by the dominance of power, access to resources, and the distribution of opportunities has hampered the realization of equitable social justice. The results show that although Pancasila normatively emphasizes the principles of equality and solidarity, its implementation is still limited by a hierarchical social system and policies that do not favor marginalized groups. Reactualizing Pancasila values as an ideology of social justice in the era of globalization is a major urgency to address inequality and strengthen social solidarity. This effort requires synergy between character education, inclusive policies, and community empowerment so that social justice can become a substantive reality, not just an ideological symbol. Thus, this study emphasizes the need.